Kurikulum dan Problematika Pendidikan dalam Perspektif Filsafat Pendidikan Islam - El-Yunusi, Muhammad Yusron Maulana; Azizah, Cholifatul; Nabillah, Sayyid Qutub (MASALIQ, 2023)
In the view of Islamic Education Philosophy, the curriculum is created on the basis of what is contained in the Al-Qur'an and Hadith which mutually reinforce and strengthen. It is with these guidelines that we as humans obtain enlightenment and instructions to become leaders on earth and live a good life in this world and the hereafter, through a process, namely education primarily in Islamic education. Then, in Islamic education, this cannot be separated from the name of the curriculum, the existence of a curriculum is nothing but the birth of education that is knowledgeable, has character, and has skills. In addition to having an educational curriculum, besides that, there are also certain problems that must be faced, but this can also be used as evaluation material and further developed with good, Apart from support, education always goes smoothly but surely there are obstacles or problems that must be faced. Therefore education must really carried out as well as possible for the sake of creating a generation that is intellectual and behaves politely. So must be conveyed in a mature and relevant scientific substance.